Changes in Dopamine Transmission in the Nucleus Accumbens Shell and Core during Ethanol and Sucrose Self-Administration - Bassareo, Valentina; Cucca, Flavia; Frau, Roberto; Di Chiara, Gaetano (Frontiers in Behavioral Neuroscience, 2017)
Ethanol, like other substances of abuse, preferentially increases dopamine (DA) transmission in the rat nucleus accumbens (NAc) following passive administration. It remains unclear, however, whether ethanol also increases NAc DA transmission following operant oral self-administration (SA). The NAc is made-up of a ventro-medial compartment, the shell, and a dorso-lateral one, the core, where DA transmission responds differentially following exposure to drugs of abuse. Previous studies from our laboratory investigated changes in dialysate DA in the NAc shell and core of rats responding for sucrose pellets and for drugs of abuse. As a follow up to these studies, we recently investigated the changes in NAc shell and core DA transmission associated to oral SA of a 10% ethanol solution. For the purpose of comparison with literature studies utilizing sucrose+ethanol solutions, we also investigated the changes in dialysate DA associated to SA of 20% sucrose and 10% ethanol+20% sucrose solutions. Rats were trained to acquire oral SA of the solutions under a Fixed Ratio 1 (FR1) schedule of nose-poking. After training, rats were monitored by microdialysis on three consecutive days under response contingent (active), reward omission (extinction trial) and response non-contingent (passive) presentation of ethanol, sucrose or ethanol+sucrose solutions. Active and passive ethanol administration produced a similar increase in dialysate DA in the two NAc subdivisions, while under extinction trial DA increased preferentially in the shell compared to the core. Conversely, under sucrose SA and extinction DA increased exclusively in the shell. These observations provide unequivocal evidence that oral SA of 10% ethanol increases dialysate DA in the NAc, and also suggest that stimuli conditioned to ethanol exposure contribute to the increase of dialysate DA observed in the NAc following ethanol SA. Comparison between the pattern of DA changes detected in the NAc subdivisions under sucrose and ethanol SA likewise suggests that the NAc shell and core DA play different roles in sucrose as compared to ethanol reinforcement.